Incomplete reperfusion and the presence of distal emboli in predicting clinical outcome after endovascular thrombectomy - Lei Feng; Eric Sauvageau; David S Liebeskind; Amin Aghaebrahim; Gerard Deib; Christian Ulfert; Alejandro M Spiotta; Jérome Berge; Xavier Barreau; Bruno Bartolini; Francesco Puccinelli; Guillaume Saliou; et al. (BMJ Surgery, Interventions, & Health Technologies)
Objectives To explore the relationship between final expanded treatment in cerebral infarction (eTICI) score and the presence or absence of distal emboli on final angiography on clinical outcome after endovascular thrombectomy (EVT) for acute ischaemic stroke (AIS). Persistent distal emboli on angiography are commonly noted, yet not all patients with intermediate eTICI scores demonstrate clear angiographic emboli, raising the possibility that these angiographic differences may correlate with distinct mechanisms of ‘no-reflow’. Therefore, we sought to better understand the potential clinical impact of such angiographic markers in cases of incomplete reperfusion.Design We performed an exploratory retrospective analysis of a prospectively collected group of AIS patients who underwent EVT for M1 occlusions using the ASSIST Registry.Setting 71 sites in 11 countries participated in the registry.Participants A total of 650 patients with M1 occlusions were included.Main outcome measures We compared 90-day modified Rankin scale (mRS) scores based on eTICI score as well as the presence or absence of distal emboli on final angiography.Results Clinical outcome based only on eTICI score revealed a shift in 90-day mRS, with a significant difference across eTICI scores in predicting 90-day mRS 0–2. In the intermediate eTICI grades 2b67 and 2c, there was a trend towards better 90-day mRS when emboli were present on final angiography than when emboli were absent. However, pairwise comparisons between these levels were non-significant.Conclusion In patients with final eTICI 2b67 or 2c, those with persistent emboli trended towards better clinical outcomes. With intermediate eTICI reperfusion, identifying the presence or absence of distal emboli on final angiography may be useful in distinguishing patterns of incomplete reperfusion. These findings should be followed by investigations on correlation between angiography and other markers of microcirculatory ‘no-reflow’.Trial registration number NCT03845491.